Fire appliances replacement system at the Fire and Rescue Department Malaysia - Tuan Muda, Tuan Ab Rahman (1999)
The Fire and Rescue Department Malaysia are expending its fire fighting and rescue operations in the air with the purchasing of2 helicopters units in 1998. But as far as fire appliances are concerned, they are lagging far behind because more than 50 % the water tenders in service are too old and inadequate for the increasing workloads at busy fire stations throughout the country. Managements are faced with budget constraints to replace the appliances that are exceeding 10 years of service according to the adopted replacement system and also to provide additional appliances with the opening of new fire stations. Due to the shortage of the water tenders, units that are not reliable are still press in service and kept as front line fighting appliances by the Department. The results shows that Nissan water tenders which are relatively new are capable of meeting the demands of busy fire stations in terms of high annual mileage, low maintenance costs and high availability performance. In contrast, Bedford water tenders that are more than 15 years in service are for limited usage, unreliable and costly to maintain and as a results greatly affected the capability of the fire fighting and rescue works carried out by the Department. The adoption of the fire appliances replacement system created a commitment of future capital spendings and offered the prospect of a modern fleet that are equipped with the latest improvements in safety, efficiency and performance.